Balance, executive functions and falls in elderly with Alzheimer's disease (AD): A longitudinal study - Pedroso, Renata Valle [UNESP]; de Melo Coelho, Flavia Gomes [UNESP]; Santos-Galduroz, Ruth Ferreira [UNESP]; Riani Costa, Jose Luiz [UNESP]; Gobbi, Sebastiao [UNESP]; Stella, Florindo [UNESP] (Elsevier B.V., 2012)
Elderly individuals with AD are more susceptible to falls, which might be associated with decrements in their executive functions and balance, among other things. We aimed to analyze the effects of a program of dual task physical activity on falls, executive functions and balance of elderly individuals with AD. We studied 21 elderly with probable AD, allocated to two groups: the training group (TG), with 10 elderly who participated in a program of dual task physical activity; and the control group (CG), with 11 elderly who were not engaged in regular practice of physical activity. The Clock Drawing Test (CDT) and the Frontal Assessment Battery (FAB) were used in the assessment of the executive functions, while the Berg Balance Scale (BBS) and the Timed Up-and-Go (TUG)-test evaluated balance. The number of falls was obtained by means of a questionnaire. We observed a better performance of the TG as regards balance and executive functions. Moreover, the lower the number of steps in the TUG scale, the higher the scores in the CDT, and in the FAB. The practice of regular physical activity with dual task seems to have contributed to the maintenance and improvement of the motor and cognitive functions of the elderly with AD. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Falls and cognitive performance; Executive functions in elderly; Balance in elderly; Physical activity of elderly